Stress differentially regulates brain expression of corticotropin-releasing factor in binge-like eating prone and resistant female rats. (1st December 2016) - Calvez, Juliane; de Ávila, Camila; Guèvremont, Geneviève; Timofeeva, Elena
Abstract: The expression of corticotropin-releasing factor (CRF), a neuropeptide that regulates endocrine and behavioral responses to stress, was assessed in the brain in rats prone or resistant to stress-induced binge-like eating of sucrose. Female Sprague-Dawley rats were subjected to unpredictable intermittent 1-h access to sucrose in non-stressful conditions or after exposure to three foot shock stress sessions. Experimental sessions were performed at metestrus, diestrus, and proestrus. The rats were assigned to the binge-like eating prone (BEP) or the binge-like eating resistant (BER) phenotypes according to the rats' persistently high or low sucrose intake following three stress sessions. The BEP rats displayed elevated consumption of sucrose in non-stressful conditions and an additional significant increase in sucrose intake in response to stress. Conversely, the BER rats showed lower sucrose intake in non-stressful conditions, and stress did not increase sucrose intake in this phenotype. The brain expression of CRF mRNA and plasma corticosterone levels were assessed 30 min after the last stress session at the diestrous phase of the estrous cycle. Stress triggered a significant increase in plasma corticosterone levels and strongly increased CRF mRNA expression in the paraventricular hypothalamic nucleus in the BER but not in the BEP rats. However, the BEP but not the BER rats demonstrated a significant increase in CRF mRNA expression in the bed nucleus of the stria terminalis (BNST) after stress. Hyporeactivity of the hypothalamic-pituitary-adrenal axis and the higher CRF expression in the BNST in BEP rats may contribute to stress-induced binge-like sucrose eating in the BEP phenotype. Graphical abstract: